Hubungan Riwayat Keluaga, Jenis Pekerjaan, dan Tingkat Stress Terhadap Kejadian Hipertensi Di Dusun Kebonkalapa, Kutapohaci - Afifah Miranda Putri; Linda Riski Sefrina; Milliyantri Elvandari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Degenerative diseases are chronic diseases that can affect a person's quality of life in the future. One example of degenerative diseases is diabetes mellitus and hypertension. Hypertension is defined as one of the most dangerous health problems worldwide because hypertension is a major risk factor that can cause cardiovascular diseases such as heart attack, heart failure, stroke. The purpose of this study was to determine the relationship between family history, type of work, and stress level on the incidence of hypertension in Kebonkalapa hamlet, Kutapohaci. The research method used a nonparametric test technique using the chi square statistical test and was processed using the IBM SPSS 25 application. The results of the analysis obtained from this study found that family history, type of work, and stress level were not associated with the incidence of hypertension in Kebonkalapa hamlet, Kutapohaci because the p-value was greater than 0.05.